DROUGHT EFFECTS ON LEAF CANOPY TEMPERATURE AND LEAF SENESCENCE IN BARLEY - Mahmood, Y. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Drought stress is a major threat on most of the agricultural crops grown in the East Mediterranean Region in the consequence of predicted global climate change (1). Therefore, improving essential cereal crops such as barley is extremely important for this region to increase yield production due to its economic interest and adaptability to dry environments (29). This two-year experiment was carried out in Kalar technical institute, in Garmian region, Iraq during the seasons of 2016-17 and 2017-18. Canopy temperature depression (CTd) and leaf senescence traits (Onset of leaf senescence (SENonset) and End of leaf senescence (SENend)) were evaluated under irrigated and rain-fed conditions for five hybrid genotypes of barley. Canopy temperature was increased by drought by almost one degree Celsius on average for both years (P=0.002). Leaf senescence durations were also affected by water stress and advanced SENonset by around 34% (P=0.001) and SENend by around 10% (P=0.01) averaging over years. Genotypes 3//14 scored the highest canopy temperature depression and the latest onset of leaf senescence under drought for the cross year mean (P=0.05). Genotype 3//5 was also the latest to reach the end of leaf senescence averaging over years. Genotypes 3//14, 3//5 and 3//4 were generally appeared to have cooler canopy and later onset of leaf senescence than the genotypes 3//18 and 3//1 indicating the capability of these genotypes to have a better performance under water limitations comparing to other genotypes. Canopy temperature depression was positively associated with onset of leaf senescence under drought conditions averaging over years (R2=0.89; P=0.02), but not under irrigated conditions (R2=0.45; P=0.21). There was also a trend for a positive association between canopy temperature and the end of leaf senescence under drought conditions (R2=0.59; P=0.13) in 2018. These associations might be linked to genetic variations in water uptake and/or water-use efficiency.